Does Digital Strategy Disclosure Improve Operational Profitability? Text-Mining Evidence from Indonesia's Large-Cap Firms, 2019–2024 - Delfi Gunardy; Siska Noviaristanti (PT. Publikasiku Academic Solution, 2026)
The productivity paradox, the puzzle that intensive digital investment does not always translate into observable efficiency gains, remains an underexamined issue in emerging-market corporate practice. Background: While corporate annual reports of large Indonesian firms increasingly feature digital strategy language, it is unclear whether this narrative intensity coincides with measurable improvements in asset-based profitability. Purpose of the Study: This paper asks whether the intensity with which firms communicate their digital strategy in annual reports is reflected in Return on Assets (ROA) among Indonesia’s largest publicly listed companies. Methods: We develop a reproducible bilingual text-mining procedure to score the digital-strategy intensity (DGS) of annual reports from the 50 largest IDX-listed firms for the fiscal years 2019 through 2024, generating a strongly balanced firm-year panel of 300 observations. The DGS is normalized by document length to control for narrative volume. We estimate firm-and-year fixed-effects panel regressions of ROA on DGS with firm-clustered robust standard errors, and we conduct sensitivity analyses based on one-year lags, pandemic versus post-pandemic sub-periods, and leave-one-control-out perturbations. Results: The within-firm association between DGS and ROA is statistically indistinguishable from zero. The point estimate is small and directionally negative, consistent with the productivity-paradox conjecture that short-run adjustment costs of digital initiatives may temporarily depress asset productivity before any payoff appears. Leverage emerges as the only consistent within-firm predictor of ROA, and the 2020 dummy captures a sharp pandemic-related profitability shock. Conclusions: Disclosure-based digital intensity should be read as a marker of strategic orientation, not as evidence of realized operational gains. The findings document an implementation gap between digital narrative and asset productivity in the Indonesian large-cap segment and supply a methodological foundation for subsequent studies that examine valuation effects and complementary-asset moderators.